2021
DOI: 10.1088/1361-648x/abee3b
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic structure and crystal field excitations of NdOs2Al10: a neutron scattering study

Abstract: We have investigated the magnetic properties of a polycrystalline sample of NdOs2Al10 using neutron diffraction and inelastic neutron scattering, magnetic susceptibility and heat capacity measurements. The magnetic susceptibility data reveal an antiferromagnetic transition at T N1 = 2.2 K while the heat capacity data which extend to lower temperatures show a further transition at T N2 = 1.1 K. The INS measurements detect four well-resolved crystal field excitations at 7.4, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…An optical conductivity measurement on CeOs 2 Al 10 has revealed that a charge-density-wavelike instability which develops along the b axis at temperatures slightly higher than T N induces unconventional AFM ordering [16]. This mechanism contrasts with conventional RKKY dominated ordering as in the case of GdT 2 Al 10 [7,27] and NdOs 2 Al 10 [28]. The orthorhombic crystalline-electric field experienced by the f electrons was also proposed to be an important driver for the strong magnetic anisotropy and the small ordered magnetic moments in CeT 2 Al 10 [2,9,[29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…An optical conductivity measurement on CeOs 2 Al 10 has revealed that a charge-density-wavelike instability which develops along the b axis at temperatures slightly higher than T N induces unconventional AFM ordering [16]. This mechanism contrasts with conventional RKKY dominated ordering as in the case of GdT 2 Al 10 [7,27] and NdOs 2 Al 10 [28]. The orthorhombic crystalline-electric field experienced by the f electrons was also proposed to be an important driver for the strong magnetic anisotropy and the small ordered magnetic moments in CeT 2 Al 10 [2,9,[29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…An optical conductivity measurement on CeOs 2 Al 10 has revealed that a charge-density-wave like instability which develops along the b axis at temperatures slightly higher than T N induces unconventional AFM ordering [16]. This mechanism contrasts with conventional RKKY dominated ordering as in the case of GdT 2 Al 10 [7,27] and NdOs 2 Al 10 [28]. The orthorhombic crystallineelectric field experienced by the f -electrons was also proposed to be an important driver for the strong magnetic anisotropy and the small ordered magnetic moments in CeT 2 Al 10 [2,9,[29][30][31].…”
Section: Introductionmentioning
confidence: 99%